A Literature Review and Analysis of Prison Offences and Punishments in England and Wales in 2007 by Gender - Phillips, Catharine (2009)
It is commonly agreed by scholars, members of the criminal justice system and the general public that court imposed sentences at times differ depending on the gender of the offender. However, there has been little empirical research conducted in regards to gender differences related to offending and discipline within prisons. The few published studies have reported contradictory results. Prison discipline is an essential part of upholding the good order and security of prisons along with maintaining the safety of prison staff, visitors, prisoners and the general public. The proposed research will identify any discrepancies between the punishments handed to male and female prisoners within the United Kingdom (England and Wales) for infractions of prison legislation. Available data provided by the United Kingdom prison service will be examined and a comparison made between the disciplinary offences committed, and subsequent punishments incurred by, male and female prisoners. The results in relation to the rates of offending and punishments will then be discussed in further detail. In addition, information will be provided in regards to the current legislation surrounding prison offences in the Western Australian prison system, with the aim being to highlight differences and similarities in prison legislation in Western Australia and the United Kingdom